Figuring Out Root and Epistemic Uses of Modals: The Role of the Input. (26th August 2022) - van Dooren, Annemarie; Dieuleveut, Anouk; Cournane, Ailís; Hacquard, Valentine
Abstract: This paper investigates how children figure out that modals like must can be used to express both epistemic and "root" (i.e. non epistemic) flavors. The existing acquisition literature shows that children produce modals with epistemic meanings up to a year later than with root meanings. We conducted a corpus study to examine how modality is expressed in speech to and by young children, to investigate the ways in which the linguistic input children hear may help or hinder them in uncovering the flavor flexibility of modals. Our results show that the way parents use modals may obscure the fact that they can express epistemic flavors: modals are very rarely used epistemically. Yet, children eventually figure it out; our results suggest that some do so even before age 3. To investigate how children pick up on epistemic flavors, we explore distributional cues that distinguish roots and epistemics. The semantic literature argues they differ in "temporal orientation" (Condoravdi, 2002 ): while epistemics can have present or past orientation, root modals tend to be constrained to future orientation (Werner 2006 ; Klecha, 2016 ; Rullmann & Matthewson, 2018 ). We show that in child-directed speech, this constraint is well-reflected in the distribution of aspectual features of roots and epistemics, but that the signal might be weak given the strong usage bias towards roots. We discuss (a) what these results imply for how children might acquire adult-like modal representations, and (b) possible learning paths towards adult-like modal representations.